Guide to the marine sport fishes of Atlantic Canada and New England - Coad, Brian W. (Heritage., 1992)
Atlantic Canada and northern New England have a great diversity of fishes providing both food and sport. Their waters are home to more than 600 kinds of fished, of which 70 are of sporting, culinary, or bait-fish interest. Brian W. Coad provides a convenient and comprehensive guide to these fishes.